The Race Problem and Presbyterian Union - Reimers, David M. (Church history, 1962)
After nearly a century of division the Presbyterian Church in the United States (the southern church) and the Presbyterian Church in the United States of America (the northern church) attempted to unite in 1954. The southern Presbyterians voted against the merger and kept America's two largest Presbyterian bodies divided. Although little was said concerning race relations during the debates on unification, there is reason to believe that the race issue was extremely important in the defeat of the plan in the South. Two sociologists, perhaps exaggerating, have concluded that it was the key factor in the failure of union. In 1955 the moderator of the southern church told the General Assembly of the North that he felt the Negro question, in particular the Supreme Court's decision on school desegregation, affected the vote; and the organ of the North, Presbyterian Life, echoed this opinion.